O papel da política fiscal no enfrentamento da desigualdade de gênero e raça no Brasil - Fernando Gaiger Silveira; Luana Passos; Matias Cardomingo; Jo\~ao Pedro de Freitas Gomes; Ruth Pereira Di Rada; Luiza Nassif Pires; Pedro Romero Marques (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This text examines the distributive effects of fiscal policy in Brazil by considering it according to gender and race criteria. Based on the Brazilian Consumer Expenditure Survey (POF) of 2017/2018, we assess how cash transfers, indirect taxes and direct taxes impact income by strata among four groups: white men, white women, black men and black women. In addition, we disaggregate income distribution to consider the top 1% of earners separately. Our findings indicate that the black population is relatively more penalized by the Brazilian tax system. It stems from the relative predominance of indirect taxation and its regressivity. Conversely, direct taxation is progressive and affects men and the white population proportionally more. However, as it represents a reduced share of total tax revenues, it is not capable of mitigating indirect taxation effects. Regarding cash transfers, we observe a pro-poor, pro-women, and pro-black effect. Finally, the analysis of the top 1% indicates a falling progressivity of direct taxation among white men, which does not occur among black men. This result might arise from the nature of the top income appropriated by the categories: while black men tend to rely mainly on labour income, white men are more prone to receive capital income.
Keywords: D31; H22; J1; 330; fiscal redistribution; tax progressivity; cash transfers; race and gender inequalities